2016
DOI: 10.2147/cia.s107285
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of daily teriparatide in a prospective observational study in patients with osteoporosis at high risk of fracture in Japan: final report

Abstract: This postmarketing surveillance study assessed the safety and effectiveness of teriparatide in patients with osteoporosis at high risk of fracture in Japan. The patients received teriparatide 20 μg daily by subcutaneous injection, for a maximum of 24 months. Safety and effectiveness analyses were based on data from 1,847 patients who were predominantly female (92.6%) with a mean age of 75.4 years. A total of 157 adverse drug reactions (ADRs) were reported in 140 (7.58%) patients; the most common ADRs were hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
0
26
0
1
Order By: Relevance
“…In 2005, ∼13% of the Japanese adult population were estimated to have CKD and this figure is likely to be even higher in the elderly 6,7. Osteoporosis and early-stage CKD frequently coexist and ∼20% of patients with osteoporosis have stage 3 or 4 CKD 8. Further, osteoporosis and CKD are among the most common age-related comorbidities that independently impair bone strength 911.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2005, ∼13% of the Japanese adult population were estimated to have CKD and this figure is likely to be even higher in the elderly 6,7. Osteoporosis and early-stage CKD frequently coexist and ∼20% of patients with osteoporosis have stage 3 or 4 CKD 8. Further, osteoporosis and CKD are among the most common age-related comorbidities that independently impair bone strength 911.…”
Section: Introductionmentioning
confidence: 99%
“…A 24-month postmarketing surveillance (PMS) study demonstrated the safety and effectiveness of daily teriparatide in 1,847 patients with osteoporosis at high risk of fracture in Japan 8. Most (92.6%) patients included in the original PMS study were female and postmenopausal (90.8%), with a mean age of 75.4 years 8.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations